Challenges en route to digital transformation - Tay, Bee Hoong (Universiti Teknologi MARA, Terengganu, 2019)
With the arrival of the Fourth Industrial Revolution (IR4.0), firms are bounded to transform to the next level of competition, i.e. the digital realm. According to an article by Bank Negara Malaysia on ‘Unlocking Malaysia’s Digital Future: Opportunities, Challenges and Policy Responses’, digital technologies are now wide-spread and pervasive with new opportunities emerged beyond e-commerce to robots and artificial intelligence (Al), which are quickly becoming indispensable in some industries. The 2018 OECD report on G-20 Finance Ministers highlights that technological advances during the recent industry revolution will transform the production and distribution of goods and services over the next 10 to 15 years. Thus, large productivity gains can be realized by accelerating the technology adoption and diffusion, with the corresponding investments in human and management skills as well as digital infrastructure. Therefore, Malaysian entrepreneurs need to accelerate the adoption of digital technology in their businesses in order to be able to withstand competition, gain Malaysian firms, particularly the small to medium enterprises (SMEs) are important growth drivers of Malaysian economy which represent 98.5% of total business establishments in Malaysia, according to the SME report. The same report documented that SMEs contributed 37.1% of overall GDP growth in 2017. Although the digital transformation may offer opportunities to advance, SMEs are facing numerous uncertainties in this journey as the impacts of new technology may challenge the traditional business path and create disruptions to the related industries.